Fluid overload is an independent risk factor for acute kidney injury in critically Ill patients: results of a cohort study. Issue 1 (December 2017) - Salahuddin, Nawal; Sammani, Mustafa; Hamdan, Ammar; Joseph, Mini; Al-Nemary, Yasir; Alquaiz, Rawan; Dahli, Ranim; Maghrabi, Khalid
Abstract Background Acute Kidney injury (AKI) is common and increases mortality in the intensive care unit (ICU). We carried out this study to explore whether fluid overload is an independent risk factor for AKI. Methods Single-center prospective, observational study. Consecutively admitted, ICU patients were followed for development of AKI. Intravenous fluid volumes, daily fluid balances were measured, hourly urine volumes, daily creatinine levels were recorded. Results Three hundred thirty nine patients were included; AKI developed in 141 (41.6%) patients; RISK in 27 (8%) patients; INJURY in 25 (7%); FAILURE in 89 (26%) by the RIFLE criteria. Fluid balance was significantly higher in patients with AKI; 1755 ± 2189 v/s 924 ± 1846 ml, p < 0.001 on ICU day 1. On multivariate regression analysis, a net fluid balance in first 24 h of ICU admission, OR 1.02 (95% CI 1.01, 1.03p = 0.003), percentage of fluid accumulation adjusted for body weight OR1.009 (95% CI 1.001, 1.017, p = 0.02), fluid balance in first 24 h of ICU admission with serum creatinine adjusted for fluid balance, OR 1.024 (95% CI 1.012, 1, 035, p = 0.005), Age, OR 1.02 95% CI 1.01, 1.03, p < 0.001, CHF, OR 3.1 (95% CI 1.16, 8.32, p = 0.023), vasopressor requirement on ICU day one, OR 1.9 (95% CI 1.13, 3.19, p = 0.014) and Colistin OR 2.3 (95% CI 1.3, 4.02, p < 0.001) were significant predictors of AKI. There was no significant association between fluid type; Chloride-liberal, Chloride-restrictive, and AKI. Conclusions Fluid overload is an independent risk factor for AKI.